Faktor-Faktor yang Berhubungan dengan Kejadian Anemia pada Ibu Hamil di Puskesmas Julok Aceh Timur Tahun 2024 - Fitriani Fitriani; Ester Simanullang; Nur Azizah (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Indonesia's maternal mortality rate (MMR), at 189 per 100,000 live births, is higher than countries in Southeast Asia such as Malaysia, Brunei, Thailand and Vietnam. Indonesia's newborn mortality rate is the third highest in Southeast Asia at 9.3 per 1,000 live births. In 2022 to 2023, there was an increase in the number of maternal deaths from 4,005 to 4,129, and the number of newborn deaths from 20,882 to 29,945 (Ministry of Health, 2023). Anaemia in pregnant women can increase the risk of premature birth, maternal and child mortality, and infectious diseases. Iron deficiency anaemia in mothers can affect fetal/baby growth and development during pregnancy and afterwards. This study is a type of quantitative research using a case control design. The research that has been done shows that most respondents experienced mild anaemia 20 people (66.7%), moderate anaemia 7 people (23.3%) and who did not experience anaemia only 3 people (10%). Most of the respondents, 83.3%, did not make routine ANC visits and 83.3% also had a poor diet. There is a significant relationship between ANC visits (p=0.000), diet (p=0.002) with the incidence of anaemia in pregnant women at the Puskesmas in 2019.